ANALISIS PENGARUH HARGA KOMPETITIF,FASILITAS DAN KETERSEDIAAN PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA KONSUMEN SALON MOBIL AUTOWAX SEMARANG - Yuliardi, Farid Meraz; Khasanah, Imroatul (Faculty of Economics and Business Diponegoro University, 2015)
This study aimed to analyze the effect of competitive pricing to the customer's satisfaction on products and services salon car autowax semarang, to analyze the effect of the facility to the customer's satisfaction on products and services salon car autowax semarang, to analyze the impact of service quality to customer satisfaction on the products and services of the salon car autowax semarang.The samples used were 100 respondents who are consumers in the salon car autowax semarang. Tool data collection using questionnaires. The analysis technique used regression analysis to test the validity and reliability.